Human Resource Development in Research Governance in Regional Research and Innovation Agencies Makassar City - Dedy Herianto; Badu Ahmad; Muh. Akmal Ibrahim; Hasniati Hasniati (Universitas Pancasakti, 2026)
Problems in study This leave from Not yet optimally capacity source Power man in governance​ research at the Makassar City Regional Research and Innovation Agency. Conditions the seen from Still limited power functional researchers and analysts policy, not yet evenly distributed training based competence research, not yet proportionally award to burden Work substantive researchers, limitations facilities and data access, as well as Not yet optimally planning recruitment apparatus based on need institutional. Research objectives This is For analyze improvement capacity in governance​ research at the Makassar City Regional Research and Innovation Agency, especially in the dimensions development source Power human beings that include training, salary, conditions work, and recruitment. Research This use method qualitative with approach phenomenological through interview in-depth, observation field, and review document. Research conclusion show that improvement capacity source Power man in governance​ research Not yet walk in a way systematic, planned, and sustainable. Strengthening capacity need directed at training based need research, system more incentives​ fair and based performance, improvement condition supportive work​ activity research, as well as recruitment based competence. In perspective theory improvement Grindle capacity, development source Power man become foundation important for strengthening organizational and institutional reform research area.